1995
DOI: 10.1111/j.1464-5491.1995.tb00449.x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Second‐generation Electrochemical Blood Glucose Monitoring System

Abstract: One hundred and ninety-five diabetic patients attending hospital clinics gave blood samples to test the accuracy and precision of a second generation glucose sensor (satellite G, MediSense Inc., Abingdon, UK) with particular emphasis on its performance with venous blood. Sensor results correlated closely with a standard laboratory method; analysis of residuals showed no deviation from zero slope. Mean percentage difference was low (< +/- 6.0%) and the 95% limits of agreement were < +/- 30% with both capillary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
2
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…In addition, qualitative review of the tracking plots shows that the lag varies depending on whether glucose levels are rising or falling. Similar trends have been observed in continuous measurements of subcutaneous glucose obtained with implanted sensors or microdialysis devices, 4,[16][17][18][19][20] and are associated with mass transfer between the blood and peripheral tissue. However, with the biographer the primary component of the lag time is the 20-minute measurement cycle and resulting "moving average" nature of the readings.…”
Section: Commentsupporting
confidence: 75%
See 2 more Smart Citations
“…In addition, qualitative review of the tracking plots shows that the lag varies depending on whether glucose levels are rising or falling. Similar trends have been observed in continuous measurements of subcutaneous glucose obtained with implanted sensors or microdialysis devices, 4,[16][17][18][19][20] and are associated with mass transfer between the blood and peripheral tissue. However, with the biographer the primary component of the lag time is the 20-minute measurement cycle and resulting "moving average" nature of the readings.…”
Section: Commentsupporting
confidence: 75%
“…16 In addition, the biographer precision results show a mean difference and SD similar to values obtained for replicate measures of blood samples. 16 Taken together, the results of this study and the published data on performance of self-monitoring BG devices show that the accuracy of the biographer compares well with currently available devices. The close agreement between biographer readings and BG measurements also demonstrates that subcutaneous glucose is an appropriate measure of the glycemic state.…”
Section: Commentsupporting
confidence: 62%
See 1 more Smart Citation
“…However, this list (5,7-11) is incomplete, with there being many additional studies incorporating EGA (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). What is important to point out is that in all of these published studies the authors reported both EGA results and standard statistical results.…”
mentioning
confidence: 99%